Platform for Situated Intelligence - Bohus, Dan; Andrist, Sean; Feniello, Ashley; Saw, Nick; Jalobeanu, Mihai; Sweeney, Pat; Thompson, Anne Loomis; Horvitz, Eric (Microsoft, 2021)
We introduce Platform for Situated Intelligence, an open-source framework created to support the rapid development and study of multimodal, integrative-AI systems. The framework provides infrastructure for sensing, fusing, and making inferences from temporal streams of data across different modalities, a set of tools that enable visualization and debugging, and an ecosystem of components that encapsulate a variety of perception and processing technologies. These assets jointly provide the means for rapidly constructing and refining multimodal, integrative-AI systems, while retaining the efficiency and performance characteristics required for deployment in open-world settings.